High wire : the precarious financial lives of American families - Gosselin, Peter (Peter G.) (Basic Books, 2009)
The U.S. economy has had 25 years of some of the strongest, smoothest growth in its history--economists have even named it: "the Great Moderation." So why have so many of us arrived at the new century with a gnawing sense that events are moving against our families and ourselves? Drawing on interviews with hundreds of Americans and new statistics he developed, economics journalist Gosselin traces a quarter-century shift of economic risk from the broad shoulders of business and government to the backs of working people, a shift that has shaken the pillars of most families' lives--stable jobs, solid benefits, government protections. The change means that the benefits of growth come at greater peril, and your financial fall will be steeper if you stumble. This threat to working Americans' security--and what to do about it--is a pressing concern to economists, policy-makers, and everyone who works for a living.--From publisher description